Evolution of Pediatric Urology at Sindh Institute of Urology and Transplantation - Sultan, Sajid (Frontiers in Pediatrics, 2014)
Sindh Institute of Urology and Transplantation was started in 1972 as an eight bedded department of genitourinary surgery in a government hospital by its pioneer and present director Syed Adib ul Hassan Rizvi. Responding to the socioeconomic dynamics and the needs of the patient population the facility grew into the largest tertiary care Urology, Nephrology, and Transplant center of south Asia. One of the salient components has been the evolution of the Department of Pediatric Urology, which in itself has shown a tremendous growth into an internationally recognized center for pediatric urology services taking care of all aspects including center of excellence for pediatric stone disease. The guiding mission of this institute remains to provide free medical services at zero cost without any discrimination to all who come to its doorstep and matching with high standard of care without compromising their dignity and self-respect. This institute highlights the fact that lack of resources is no excuse and is a role model for developing countries, where national and international support, motivation, and cooperation can offer more advanced and better quality medical services to our children.